Psychometric properties of the general self-efficacy scale in a Colombian sample - Fernando Juárez (Universidad de San Buenaventura, 2008)
The self-efficacy construct has been studied from two different viewpoints. Firstly, in a specific manner, as it was originally proposed and secondly, in a generalized way, defined as an optimistic self-belief of personal capability to cope efficiently and competently with a variety of situations. In order to measure this construct at the broadest level the General Self Efficacy Scale (GSE) was designed and adapted to Spanish in Costa Rica. This study aimed at validating the scale in a Colombian sample composed of college students. Participants were also administered the Situational Personality Questionnaire (named in Spanish as Cuestionario de Personalidad Situacional, CPS) and its factors have, theoretically speaking, a certain relationship with the studied construct. According to the results, the GSE showed a high internal consistency (Cronbachs alpha value of .83). Convergent and discriminant validity of this instrument were evaluated through the CPS and positive correlations were obtained with efficacy, confidence, self-concept and emotional stability while negative correlations were obtained with anxiety. Through exploratory and confirmatory factor analysis, the unidimensional structure of the scale was validated.